ANALISIS LOW EXTERNAL INPUT SUSTAINABLE AGRICULTURE (LEISA) PADA TERNAK DOMBA DI KAWASAN AGRIBISNIS DESA TERNAK, DESA CINTALAKSANA KECAMATAN TEGALWARU, KABUPATEN KARAWANG - Achmad Firman; Linda Herlina; Slamet Yulianto (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2019)
The purpose of the research is to analyze regional carrying capacity to keep sheep in agribusiness zone at Cintalaksana village through the concept of Low External Input Sustainable Agriculture (LEISA). The village is dominated by forest and paddy land that indicate forage availabality to develop sheep commodity. The result research showed that forage availability that can be produced approaximately 4.316,93 ton dry matter per year. The amount of sheep can be kept approaximately 29.563 animal units. The analysis of carrying capacity index showed that Cintalaksana village had the carrying capacity index is 1,0002 which means that the value is in a critical category. Therefore the sheep development in Desa Cintalaksana could not support to LEISA concept because the index value is a critical category.